PENERAPAN K3 DENGAN METODE HIRARC (HAZARD INDENTIFICATION, RISK ASSESSMENT AND RISK CONTROL) PADA KONTRUKSI DRAINASE U-DITCH PROYEK TOL (STUDI KASUS : PT. RST) - Saifullah Saiful (Institut Teknologi Adhi Tama Surabaya, 2026)
PT. RST is a company engaged in the construction sector. Currently, PT. RST is participating in the construction of toll road projects. Toll road infrastructure requires water channels to maintain road quality so that it is not damaged by rainwater puddles. U-ditch drainage is used as a solution to overcome water puddles (Gustomi et al., 2023). However, the process of making u-ditch drainage requires careful preparation to prevent or minimize work accidents, because this work is categorized as high-risk work. Therefore, this study uses the Hazard Identification, Risk Assessment and Risk Control method, hereinafter referred to as HIRARC, which aims to identify potential hazards, conduct risk assessments and analyses, and determine risk control (Juraman Beatrix, 2020) using interview methods, observations, literature studies and questionnaires.The results of the study showed that there were 38 potential hazards at the work site, the impacts that occurred included minor injuries, physical injuries, fatigue, ARI due to exposure to dust and chemicals, as well as the risk of failure to lift materials and overturning heavy equipment. Risk analysis is conducted by assessing the severity and likelihood, which are then categorized into low, medium, or high risk levels. From the analysis results, 11 potential hazards were found to be in the moderate risk category, 19 potential hazards in the high category, and 8 potential hazards in the extreme category. To reduce the risk level, this study predominantly recommends engineering control, administrative control, and personal protective equipment (PPE).Keywords : HIRARC, occupational safety, risk assessment, hazard control